Scalp Acupuncture Attenuates Brain Damage After Intracerebral Hemorrhage Through Enhanced Mitophagy and Reduced Apoptosis in Rats - Liu, Peng; Yu, Xinyang; Dai, Xiaohong; Zou, Wei; Yu, Xueping; Niu, Mingming; Chen, Qiuxin; Teng, Wei; Kong, Ying; Guan, Ruiqiao; Liu, Xiaoying (Frontiers in Aging Neuroscience, 2021)
To study the effect of Scalp acupuncture (SA) on the mitophagy signaling pathway in the caudate nucleus of Sprague-Dawley rats following ICH. An ICH model was established by injecting autologous arterial blood into the caudate nucleus in 200 male Sprague-Dawley rats, which were divided into five groups: sham, ICH, 3-methyladenine group (3-MA, 30 mg/kg), SA, and SA+3-MA. Animals were analyzed at 6 and 24 h as well as at 3 and 7 d. Composite neurological scale score was significantly higher in the SA group than in the ICH group. Transmission electron microscopy showed less structural damage and more autophagic vacuoles within brain in the SA group than the ICH group. SA group showed higher levels of Beclin1, Parkin, PINK1, NIX protein and lower level of Caspase-9 in brain tissue. These animals consequently showed less neural cell apoptosis. Compared with SA group, however, the score, structural damage, and levels of mitophagy protein in the SA+3-MA group were decreased, neural cell apoptosis was increased, which suggested 3-MA may antagonize the protective effect of SA on brain in ICH rats. SA may mitigate the neurologic impairment after ICH by enhancing mitophagy and reducing apoptosis.